Bioenzyme activation preparation of Fe3O/carbon nanofibers as supercapacitor electrode materials - Jiang, Xia; Yan, Wei; Shi, Gaofeng; Cai, Wei; Lu, Shiwu; Mishra, Puranjan (Springer Science and Business Media Deutschland GmbH, 2023)
A new activation method for carbon-based pore expansion of composite materials was developed using the biocatalytic principle of amylase to hydrolyze cyclodextrin into small molecules of maltose and glucose. The composite carbon nanofiber mats were prepared by electrospinning with polyacrylonitrile (PAN), α-cyclodextrin, iron acetylacetonate as the iron oxide precursor, and hemp straw-based liquefied carbon as the electrospinning precursors. The α-cyclodextrin was hydrolyzed by medium-temperature α-amylase to generate pores, and a composite electrode material of carbon nanofibers with controlled iron oxide/porous structure was prepared through pre-oxidation and carbonization. Based on the morphology and structure of the prepared electrode materials and the electrochemical performance of three electrodes and two electrodes, it can be concluded that it is feasible to prepare electrochemical materials with the pore structure of carbon nanofibers by the enzyme pore enlarging method. Meanwhile, the FePCNF1 reaches 314 F g−1; at the current density 10 A g−1, over 75.6% of initial capacitance is retained as the current density improves from 1 to 10 A g−1 and also exhibits an excellent cycling performance with 62% capacitance retention after 15,000 times charge/discharge cycles.